Work-Family Conflict And Burnout In Turkish Banking Industry - Coban, Hatice; Irmis, Ayse (European Scientific Journal, ESJ, 2016)
Work-family conflict and burnout which have based upon organizational expectations, are discussed as management issues with regards to conduce toward adverse outcomes for individuals, organizations and even for the whole society. As a result of work overload, long and irregular working hours, pressures about performance, job insecurity which is a consequence of financial risk factors as banking industry is associated with other industries, experiencing work-family conflict and burnout may seem possible for employees working in the banking industry. Thus, the banking industry is determined as the research area. In order to make the research more specific, pronouncements of industrial unions have been investigated, and then, researcher asked to bankers, who resign or retired, as if they had problems or vocational issues related with management and organization. Information achieved by literature review and the data collected from both retired and resigned employees have shown that problems of bankers are related with antecedents of work-family conflict and burnout. After that, data was collected from 307 bankers with quantitative research method. Analyses show that both work-family conflict and burnout experienced by bankers are at the average level and the positive correlation between work-family conflict and burnout has been found.